154k views
3 votes
Please show steps
30 points
need help
please explain as much as possible

Please show steps 30 points need help please explain as much as possible-example-1
User Derek E
by
5.4k points

1 Answer

2 votes

Answer: A Yes

The polynomial remainder theorem says when we divide polynomial f(x) by x-a we'll get remainder f(a).

f(x)=x^3-3x^2-31x-72

f(8)=8^3-3(8^2)-31(8)-72

f(8)=512-3(64)-31(8)- 72 = 512-192-248-72= 0

Since f(8)=0 that means x-8 has a remainder zero when divided by f(x). In other words, it's a factor of f(x).

User Tmyklebu
by
5.5k points